(3fSNI GdSLd GdPi hLO eYdbkG Ydi GdeTGgO aj YfHQ ehdGfG GdMGces - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hGdYGbHI def JjbX ef hSf GdZGadjf CeG HYO CjgG GdfGS abO SHb Zdjce ef GdhYO hGdhYX hGdhYjO ef hdi CeQce s
(3BNQgG (B:s
(3MQGe MQGe Ydi ef dGjfSNgG Ch jbQCgG Ydi GdJhGHjf ai LGeY CSad hMQGe MQGe Ydi ef bOQ Ydi fSNgG hbUQ hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi MhGTi GdfSNI JaSjQGJ dHYV YHGQGJ GdeJf ecJhHI HGdbde GdCMeQs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds